Desarrollo de un modelo de control y seguimiento de inventario en la cooperativa de producción cafetalera los ángeles para contribuir al mejoramiento de la productividad y competitividad - Pincay Suarez, Cindy Pamela (2023)
This research aimed to develop an inventory control and monitoring model for the Los Ángeles Coffee Production Cooperative, in order to improve the organization's productivity and competitiveness. The cooperative had limitations in its current inventory control system, as it was done manually, which generated inaccuracies and inefficiencies. Faced with this problem, an analysis of the inventory was carried out, identifying the products and quantities handled. Then, a manual of procedures and policies for inventory management was prepared. Finally, a model was designed that included tools such as ABC customer classification, warehouse layout, management indicators and EOQ and reorder point inventory models. The implementation of this model will significantly strengthen the control and traceability of the coffee flow, facilitating decision making, production planning and reducing operating costs. The improvement of inventory management will boost the productivity and competitiveness of the Los Ángeles Coffee Cooperative.